The Intervening Role of Knowledge and Perceived Value in Relationship of Product Packaging and Purchase Intention - Sari Lestari Zainal Ridho; Habsah Haji Mohamad Sabli; Sunanto Sunanto; Ardelia Suharmanto; Rio Permata; Hengky Rosadi; Tuti Dwi Patmayanti (Penerbit Goodwood, 2026)
Purpose: This study examines the mediating roles of knowledge and perceived value in the relationship between product packaging and purchase intention within Indonesia's creative economy and business sustainability.Research Methodology: A quantitative cross-sectional survey using SEM-PLS (WarpPLS 8.0) involved 150 consumers in Palembang, Indonesia, who purchased packaged products between February and April 2025. The measurement model demonstrated adequate reliability and validity.Results: Product packaging significantly influenced knowledge (? = 0.553, p < 0.001), perceived value (? = 0.576, p < 0.001), and purchase intention (? = 0.279, p = 0.008). Perceived value significantly increased purchase intention (? = 0.519, p < 0.001), whereas knowledge showed no significant direct effect (? = 0.057, p = 0.318). The combined indirect effect was significant (? = 0.330, p = 0.002), and the model explained 57.5% of the variance in purchase intention (R² = 0.575).Conclusions: Perceived value is a stronger mediator than knowledge, suggesting that value-oriented packaging strategies are more effective than information-based approaches in encouraging purchase intention.Limitations: The study is limited to consumers in Palembang and uses a cross-sectional design, limiting causal inference and broader generalization.Contributions: This study extends the Stimulus Organism Response (SOR) framework by clarifying the distinct mediating roles of knowledge and perceived value while providing practical implications for packaging strategies in Indonesia's creative economy.